Takotsubo cardiomyopathy: another form of cardiorenal syndrome - Bill, Verena; El-Battrawy, Ibrahim; Hoffmann, Ursula; Haghi, Dariusch; Kuschyk, Jürgen; Borggrefe, Martin; Akın, Ibrahim (Angiology, 2018)
Takotsubo cardiomyopathy (TC) is a life-threatening syndrome with ambiguous pathophysiology. The interdependency between heart failure and kidney failure (KF) is well established, but the influence of KF on TC outcome is not known. This single-center cohort from January 2003 to September 2015 consisted of 114 consecutive patients with TC. They were divided into 2 groups according to the presence (n = 32, 29.6%) or absence (n = 76, 70.3%) of KF. The end point of this retrospective study was a composite of in-hospital events, all-cause mortality, rehospitalization due to heart failure, stroke, and recurrence of TC (mean follow-up: 5 years). Although there were no differences in baseline characteristics between patients with/without KF, we found a significantly higher mortality rate in those with KF, 1 (7.9% vs 21.8%, P < .05), 2 (11.8% vs 31.5%, P < .05), and 5 years (22.3% vs 43.7%, P < .05) after the index event. There were no differences in life-threatening arrhythmias, cardiogenic shock, cardiopulmonary resuscitation, and thromboembolic events in both groups at the index event. Patients with TC and KF have a much worse long-term prognosis. This is clinically relevant, but the mechanisms responsible remain to be determined.